Association between dietary inflammatory index and periodontitis in American adults: exploring the mediating role of biological aging - Hua, Haoyang; Xu, Shencong; Wang, Yifan; Zheng, Yuanna; Xiang, Fangyue (Frontiers in Nutrition, 2025)
BackgroundDietary patterns are associated with inflammatory states. However, there are few reports about its relationship with periodontitis and its mechanism. This study investigated the relationship between dietary inflammatory index (DII) and periodontitis, and the mediating role of biological aging in this relationship.MethodsData from the National Health and Nutrition Examination Survey from 2009 to 2014 were utilized, including adults aged 20 years and above. The relationship between DII and periodontitis was assessed using multivariate logistic regression analysis, and restricted cubic splines were employed to test for potential non-linear associations. Subgroup analyses were conducted to explore potential influencing factors related to DII and periodontitis. In addition, the mediating role of biological aging in dietary inflammatory indices and periodontitis was further explored.ResultsA total of 10,096 participants were included in the study. The results indicated a positive correlation between DII scores and the prevalence of periodontitis. In the fully adjusted model, participants in the highest DII quartile had a 23% higher risk of periodontitis compared to those in the lowest quartile (OR = 1.23, 95% CI: 1.01, 1.48, p = 0.04). Subgroup analysis consistently observed a positive correlation between DII and the risk of periodontitis across all subgroups. Mediation analyses suggest some direct and indirect effects of biological aging between a pro-inflammatory diet and periodontitis.ConclusionDII scores were positively associated with the prevalence of periodontitis in U.S. adults, suggesting that dietary patterns may have a significant impact on the prevalence of periodontitis. It also provides further insight into the mechanistic link between biological aging-mediated DII and the development of periodontitis.